Halide perovskites from first principles: from fundamental optoelectronic properties to the impact of structural and chemical heterogeneity - Filip, MR; Leppert, L (IOP Publishing, 2024)
Organic-inorganic metal-halide perovskite semiconductors have outstanding and widely tunable optoelectronic properties suited for a broad variety of applications. First-principles numerical modelling techniques are playing a key role in unravelling structure-property relationships of this structurally and chemically diverse family of materials, and for predicting new materials and properties. Herein we review first-principles calculations of the photophysics of halide perovskites with a focus on the band structures, optical absorption spectra and excitons, and the effects of electron- and exciton-phonon coupling and temperature on these properties. We focus on first-principles approaches based on density functional theory and Green’s function-based many-body perturbation theory and provide an overview of these approaches. While a large proportion of first-principles studies have been focusing on the prototypical ABX3 single perovskites based on Pb and Sn, recent years have witnessed significant efforts to further functionalize halide perovskites, broadening this family of materials to include double perovskites, quasi-low-dimensional structures, and other organic-inorganic materials, interfaces and heterostructures. While this enormous chemical space of perovskite and perovskite-like materials has only begun to be tapped experimentally, recent advances in theoretical and computational methods, as well as in computing infrastructure, have led to the possibility of understanding the photophysics of ever more complex systems. We illustrate this progress in our review by summarizing representative studies of first-principles calculations of halide perovskites with various degrees of complexity.